Assessing Rooting Media and Hormone on Rooting Potential of Stem Cuttings of Bougainvillea - Marasini, P.; Khanal, A . (Journal of the Institute of Agriculture and Animal Science, 2018)
An experiment was conducted at Lamjung Campus, Lamjung to assess the rooting performance and bud sprouting of Bougainvillea, an evergreen ornamental vine. The study was conducted in partially controlled environment with two factorial treatments considering factor A in four levels(coco peat + sand, sand + FYM, garden soil, garden soil + FYM and garden soil )and factor B (with and without NAA 3000ppm) were arranged in completely randomized design (CRD) with three replication during September- November, 2016. 18 cuttings having 15 cm in length with 4 buds were planted in each treatment. Root length (7.83cm) found in Sand & FYM was significantly different to other media but rooting percentage (77.77%) was found statistically at par with other media except garden soil. Effect of hormone was found non-significant on total sprouted plant, sprout diameter and number of sprouts/cuttings whereas other parameters were affected significantly. Interaction effect of rooting media and hormone significantly affects root length (11.6cm) and rooting percentage (83.33%) which was found on sand & FYM along with NAA 3000ppm followed by Garden soil & FYM in combination with NAA 3000ppm while others parameters were non-significant. Thus it is advisable to use a good rooting media along with application of NAA 3000 ppm for better rooting in cuttings.